2019
DOI: 10.1158/2326-6066.cir-18-0751
|View full text |Cite
|
Sign up to set email alerts
|

CCR4 Blockade Depletes Regulatory T Cells and Prolongs Survival in a Canine Model of Bladder Cancer

Abstract: Regulatory T-cell (Treg) infiltration can be targeted as a cancer immunotherapy. Here, we describe therapeutic efficacy of this strategy in a canine model of bladder cancer. We used dogs with naturally occurring bladder cancer to study the molecular mechanism of Treg infiltration into bladder cancer tissues and the effect of anti-Treg treatment. Tumorinfiltrating Tregs were evaluated by immunohistochemistry, and their association with prognosis was examined in dogs with bladder cancer. The molecular mechanism … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 46 publications
0
81
0
Order By: Relevance
“…Originated from the bladder epithelial cells, bladder cancer is one of the most common malignant tumors of the urinary system with high morbidity and mortality, ranking the ninth in the world [1,2]. Bladder cancer was more common in male patients and older adults according to epidemiologic data [3].…”
Section: Introductionmentioning
confidence: 99%
“…Originated from the bladder epithelial cells, bladder cancer is one of the most common malignant tumors of the urinary system with high morbidity and mortality, ranking the ninth in the world [1,2]. Bladder cancer was more common in male patients and older adults according to epidemiologic data [3].…”
Section: Introductionmentioning
confidence: 99%
“…As another strategy to modify the TME, it was recently reported that blockade of CCR4 signaling with humanized antibodies could significantly deplete Tregs in a canine model of invasive bladder cancer (52). In that study, treatment with an anti-CCR4 antibody depleted Tregs in bladder tumor tissues in dogs, and was associated with sustained tumor regression, and prolonged survival.…”
Section: Tumor Microenvironment Modificationmentioning
confidence: 99%
“…The use of anti-CCR4 antibodies enables the removal of CCR4-expressing Treg that invades the cancer tissue and could reinforce the induction of cancer-specific T cells [160]. The percentage of cancer antigen-specific cytotoxic lymphocytes has been shown to increase after treatment with an anti-CCR4 antibody from the pretreatment level in patients with adult T cell leukemia [109].…”
Section: Treg-targeting Treatmentmentioning
confidence: 99%